Mengevaluasi Prediksi Kebangkrutan Melalui Analisis Rasio Keuangan dan Metode Altman Z-Score Pada Perusahaan Farmasi Tahun 2019-2022 - Kusmindian Daryani, Ratna; Herdina, Nova (OGZ Research & Publishing, 2023)
The aim: of this research is to predict, analyze and identify the potential for bankruptcy of a company using financial ratio analysis and the Altman Z-Score method for companies in the pharmaceutical sector from 2019 to 2022 through financial report analysis. In a situation where a company faces bankruptcy, the negative impact will be felt by various parties. Therefore, we need a model for predicting the possibility of bankruptcy that can provide an initial indication to the company.Methodology: used in this research is a quantitative-based descriptive approach. The data used comes from secondary sources, namely financial reports. The data collection technique applied is through documentation techniques, and data analysis is carried out using a descriptive analysis approach.Research results: show that in the last four years, the companies studied were included in the category of potentially facing bankruptcy risk. This is because the Z-Score value produced each year is below the standards that usually apply to companies with healthy financial performance. The decline in financial ratios and Z-Score values was caused by various factors, such as a decrease in profits due to a decrease in sales, high levels of company debt, and uncertainty in managing the working capital generated by the company each year.